Paying the Ferryman: An Old Hoard from a Burial Monument of Samos - Betsiou, Atalanti (KOINON: The International Journal of Classical Numismatic Studies, 2025)
The aim of this article is the presentation of a neglected hoard containing 15 small-denomination bronze coins from the East necropolis of Samos. The hoard was deposited inside a refined bronze vessel (inkwell) with a simple bronze-sheet cover, which was meticulously laid in cist grave 2.2 It is noteworthy that the burial hoard contained a variety of bronze denominations from different mints of Asia Minor and Greece. In light of the content, it will be argued that its deposition followed a turbulent period in the history of Samos.